2019
DOI: 10.1007/s12192-018-0945-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces human olfactory ensheathing glial apoptosis by promoting mitochondrial dysfunction and activating the JNK-Bnip3-Bax pathway

Abstract: Olfactory ensheathing glia (OEG) play an important role in regulating the regeneration of an injured nervous system. However, chronic inflammation damage reduces the viability of OEG via poorly understood mechanisms. We aimed to investigate the pathological responses of OEG in response to LPS-mediated inflammation stress in vitro. The results indicated that lipopolysaccharide (LPS) treatment significantly reduced the viability of OEG in a dose-dependent fashion. Mechanistically, LPS stimuli induced mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
(82 reference statements)
5
4
0
Order By: Relevance
“…It is well known that JNK pathway plays critical roles in the promotion of cell apoptosis under high glucose environment [35]. BNIP3 has also been reported to be associated with the regulation of JNK pathway in cells [36,37]. Here, we found that high glucose stimulation activated the JNK pathway in HK-2 cells.…”
Section: Discussionsupporting
confidence: 48%
“…It is well known that JNK pathway plays critical roles in the promotion of cell apoptosis under high glucose environment [35]. BNIP3 has also been reported to be associated with the regulation of JNK pathway in cells [36,37]. Here, we found that high glucose stimulation activated the JNK pathway in HK-2 cells.…”
Section: Discussionsupporting
confidence: 48%
“…Mitochondrial dysfunction in the brain has been associated with the pathogenesis of several types of neurodegenerative diseases, including Alzheimer's disease (AD) and Parkinson's disease . Increased production of reactive oxygen species (ROS) and neurotoxins under pathological circumstances has a negative effect in mitochondrial abundance and the copy number of mitochondrial DNA (mtDNA) . Mitochondrial biogenesis plays a critical role in maintaining normal energy metabolism, mitochondrial homeostasis, and quality control .…”
Section: Introductionmentioning
confidence: 99%
“…2 Increased production of reactive oxygen species (ROS) and neurotoxins under pathological circumstances has a negative effect in mitochondrial abundance and the copy number of mitochondrial DNA (mtDNA). 3,4 Mitochondrial biogenesis plays a critical role in maintaining normal energy metabolism, mitochondrial homeostasis, and quality control. 5 Mitochondrial biogenesis is mainly regulated by the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α) and its downstream molecules nuclear respiratory factor 1 (NRF-1) and the mitochondrial transcription factor A (TFAM).…”
Section: Introductionmentioning
confidence: 99%
“…Bnip3 has been shown to suppress inflammation as well as apoptosis induced by LPS exposure in chondrocytes through the promotion of autophagy [ 30 ]. The JNK-Bnip3 pathway has been reported to act as an upstream mediator of Bax upregulation, which can be activated by LPS to induce apoptosis of human olfactory ensheathing glial cells [ 31 ]. When the JNK-Bnip3 pathway was inhibited, Bax activation by LPS was eliminated, which resulted in attenuation of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%